Ewing’s Sarcoma of the Breast in a Young Woman: A Case Report and Review of the Literature - Papi, Simona; Combi, Francesca; Segattini, Silvia; Accogli, Silvia; Palma, Enza; Gambini, Anna; Andreotti, Alessia; Luppi, Gabriele; Tazzioli, Giovanni (Frontiers in Oncology, 2022)
Ewing’s Sarcoma Family Tumors (ESFT) include classic Ewing’s sarcoma of bone, extra-skeletal Ewing’s sarcoma (EES), and malignant small cell tumor of the chest wall (Askin tumor), and soft tissue-based Peripheral Primitive Neuroectodermal tumors (pPNET). The t(11;22)(q24;q12) translocation is associated with 85% of tumors and leads to EWS-FLI-1 (Ewing’s Sarcoma -Friend Leukemia Integration-1) formation. This is a potent transforming gene, that encodes for a chimeric protein that plays a role in the genesis of Ewing’s Sarcoma and Primitive Neuroectodermal Tumors. The breast location of ESFT remains exceptional. The prognosis is among the poorest of all subtypes of breast cancer and even poorer than other extraosseous Ewing’s sarcomas. We describe the case report of a 23-year -old patient with a growing breast lump, that required an accurate and challenging diagnostic assessment and that finally resulted in a peripheral primary neuroectodermal tumor (pPNET). Through this case description and a brief narrative review of the literature, we aim at highlighting the rarity of ESFT located in the breast. Histopathological confirmation is mandatory for all growing masses of the breast, to reach a conclusive diagnosis and to plan the correct treatment. Patients with rare diagnoses should always be centralized in Breast Units, carrying out multidisciplinary meetings, and, when necessary, the diagnosis should be shared through wider National or International Registries.